Muhdas Perspektif KH. Moh. Syihabuddin Muhsin (Pemahaman Hadis-Hadis Bid’ah versi Tokoh Lokal) - Arif Nursihah (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
“Misunderstanding often causes a quarrel, even to understand traditional collection of stories relating words or deeds of Muhammad. Now, some of Moslems judge one each other just for getting title“ahl sunna” and claim other to “ahl bida’” without thinking about togetherness which is more important. Although it’s a complicative problem but has to be solved. One of the ways is reinterpreting hadith about muhdas especially by Indonesian personage. This article aims to get an Indonesian muhdas view and his understanding of hadith method.”